STRUCTURAL AND FUNCTIONAL FEATURES OF LYMPHOCYTES IN PATIENTS WITH CHRONIC KIDNEY DISEASE, GLOMERULONEPHRITIS - V. Ya. Kaminskyy; L. Ye. Kovalchuk (Ukrainian Journal of Nephrology and Dialysis, 2017)
It is necessary to develop markers of genetic screening, that will enable diagnostics of multifactorial diseases in the early stages and determine the effectiveness of their treatment. The aim of this work was to study the structural and functional features of chromatin and nuclei of peripheral blood lymphocytes in patients with chronic kidney disease, glomerulonephritis. 75 patients were examined. For cytological study smears of peripheral blood were made and conducted analysis of lymphocytes’ nuclei in interphase. Changes of the chromatin compaction, activity of nucleolar apparatus and morphologically changed nuclei were detected, reflecting the state of transcriptionally-translational process in the cell. The features of the structural and functional parameters of lymphocytes’ metabolism in patients according to sex and disease syndrome were established. Investigated cytological markers can be used for diagnostics this pathology at early stages and to evaluate the effectiveness of the treatment.